2003
DOI: 10.1080/10473289.2003.10466153
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Cloud Water Deposition at Mountain Acid Deposition Program Sites in the Appalachian Mountains

Abstract: Cloud water deposition was estimated at three high-elevation sites in the Appalachian Mountains of the eastern United States (Whiteface Mountain, NY; Whitetop Mountain, VA; and Clingman's Dome, TN) from 1994 through 1999 as part of the Mountain Acid Deposition Program (MADPro). This paper provides a summary of cloud water chemistry, cloud liquid water content, cloud frequency, estimates of cloud water deposition of sulfur and nitrogen species, and estimates of total deposition of sulfur and nitrogen at these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…An omni-direction passive collector (Aleksic and Dukett, 2010) collected cloud water samples when the following conditions were met: cloud liquid water content > 0.05 g m −3 (to indicate the pres- August-September 2014 average values 32 ± 9 38 ± 12 9 ± 8 7 ± 3 2 ± 1 11 ± 2 1.6 ± 0.5 66 ± 11 4.8 ± 0.1 3. (Baumgardner et al, 2003). Average August-September values from 2010 to 2015 are presented in Table S1 in the Supplement, and the data can be accessed at http://www.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An omni-direction passive collector (Aleksic and Dukett, 2010) collected cloud water samples when the following conditions were met: cloud liquid water content > 0.05 g m −3 (to indicate the pres- August-September 2014 average values 32 ± 9 38 ± 12 9 ± 8 7 ± 3 2 ± 1 11 ± 2 1.6 ± 0.5 66 ± 11 4.8 ± 0.1 3. (Baumgardner et al, 2003). Average August-September values from 2010 to 2015 are presented in Table S1 in the Supplement, and the data can be accessed at http://www.…”
mentioning
confidence: 99%
“…Whiteface Mountain cloud water is more acidic than rainwater, with higher sulfate and nitrate concentrations (Aleksic et al, 2009), which are attributed to fossil fuel combustion (Dukett et al, 2011). Cloud deposition of total soluble sulfur accounts for 80-90 % of total sulfur deposition during June-September (Baumgardner et al, 2003). The cloud water samples were analyzed by electrospray ionization (ESI) coupled to Fourier transform ion cyclotron resonance mass spectrometry (FTICR-MS) in negative ion mode to characterize high molecular weight oxidized organic compounds.…”
mentioning
confidence: 99%
“…Cloud deposition has been shown to be the dominant contribution to the total (cloud plus precipitation plus dry) deposition at Whiteface (Baumgardner et al, 2003), providing 80-90% of the total soluble sulfur deposition at this site for the June through September period. A more recent study (Aleksic et al, 2009) estimated that summer cloud deposition of major ions at the Whiteface summit site was 14 to 28 times higher than the summer rain deposition at the lower elevation Marble Mountain Lodge site.…”
Section: Cloud Chemistry At Whiteface Summitmentioning
confidence: 99%
“…The wet removal influences the long-range transport of aerosols and their effects on the environment Driscoll et al, 2001;Andronache 2004;Butler et al, 2005;Civerolo et al, 2010). Numerous studies at mountain sites in Eastern US were enhanced by additional data collection and documented the detailed behaviour of precipitation chemistry and its impact on high elevation ecosystems (Lynch et al, 2000;Walker et al, 2000;Driscoll et al, 2001;Collett et al, 2002;Sickles and Grimm, 2003;Baumgardner et al, 2003;Driscoll et al, 2003;Schwab et al, 2004;Butler et al, 2005;Lehmann et al, 2005;Anderson et al, 2006;Fisher et al, 2007;Civerolo et al, 2010). Many previous studies reported wet deposition results aggregated on a weekly, monthly or annual basis, suitable for robust long-term trend characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Observations in mountain areas can provide insight into: a) long-range transport of air pollutants; b) impact of acid rain on alpine forests and their response to pollution; c) fog scavenging and aerosol removal from direct cloud impact with terrain slopes; d) role of orographic convection and its effects on precipitation; e) heterogeneous ice nucleation of various aerosol types (Wrzesinsky and Klemm, 2000;Avila and Rodà, 2002;Igawa et al, 2002;Thalmann et al, 2002;Baumgardner et al, 2003;Burkard et al, 2003;Bayraktar and Turalioglu, 2005;Kim et al, 2006;Fischer et al, 2007;Budhavant et al, 2009;Calvo et al, 2012;Pawar et al, 2012;Hallar et al, 2013;Li et al, 2014;Conen et al, 2015;Weiss-Penzias et al, 2015;Sarkar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%